2007
DOI: 10.1002/pmic.200600547
|View full text |Cite
|
Sign up to set email alerts
|

Cellular processes underlying maturation of P19 neurons: Changes in protein folding regimen and cytoskeleton organization

Abstract: Embryonal carcinoma P19 cells provide an ideal model to study molecular programs along differentiation. Upon induction by retinoic acid (RA), the cells undergo a program of differentiation that generates functioning neurons within 60 h. RA induced cells that were plated as sparse (1000 cells/mm(2)) or dense (4000 cells/mm(2)) cultures showed a marked difference in the culture morphology with the dense cultures exhibiting rapid maturation and accelerated neurite outgrowth. The protein expression levels of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…Among the identified proteins, PTPN13, CLTC, MVP, PTK2, NONO, TUBB, TUBA3, and ACTB were shared, whereas others were cell line-specific. TT cells showed a prevalence of cytoskeletal proteins, including SPTAN1, the F-actin cross-linking protein ACTN4, the cellular myosin FLJ13881, the actin binding protein LIMA1, ACTB, ACTG1, and DBN1, which is involved in cytoskeleton remodeling along axons branching in neurons [27]. Consistent with previous data [21], TT oncogenic signaling appears to be centered on SHC, PI3K, and PTK2 phosphoproteins.…”
Section: Proteomics Study Of Mtcssupporting
confidence: 71%
“…Among the identified proteins, PTPN13, CLTC, MVP, PTK2, NONO, TUBB, TUBA3, and ACTB were shared, whereas others were cell line-specific. TT cells showed a prevalence of cytoskeletal proteins, including SPTAN1, the F-actin cross-linking protein ACTN4, the cellular myosin FLJ13881, the actin binding protein LIMA1, ACTB, ACTG1, and DBN1, which is involved in cytoskeleton remodeling along axons branching in neurons [27]. Consistent with previous data [21], TT oncogenic signaling appears to be centered on SHC, PI3K, and PTK2 phosphoproteins.…”
Section: Proteomics Study Of Mtcssupporting
confidence: 71%
“…As shown in Fig. 2A, ␣-and ␤-cardiac myosin heavy chains, the markers of cardiomyocytes (35), were specifically detected in the DMSO-treated 16-day cultured P16CL6 cells and mouse cardiac muscles as a positive control. In addition, mouse monoclonal antibody MF20 reacted specifically with differentiated cardiomyocytes (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…4C. In the case of P19C6 cell differentiation into neural cells, it was revealed that 12 glycoforms (peak numbers 20,27,28,35,41,43,53,60,65,66,69, and 73) were identified as bisect type (BS) N-glycans among 13 N-glycans that increased more than 5-fold after differentiation (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…The sample protein concentration was measured using a BCA protein assay kit (Pierce), and equal quantities were loaded onto an SDS-polyacrylamide gel. Following the electrophoresis, standard Western blotting protocol including detection using an enhanced chemiluminescence detection kit (EZ-ECL, Biological Industries) was applied (26). For immunofluorescence detection, cells were grown on glass coverslides, fixed with 4% paraformaldehyde, and incubated with the appropriate secondary antibodies conjugated with fluorescent dyes Cy3 and Cy5 (Jackson Immunoresearch).…”
Section: Methodsmentioning
confidence: 99%